共同希望语言学院2022届学生对汉语多项定语顺序的掌握程度分析 - Wellian, Welli; Lina, Lina (Journal of Maobi, 2025)
Attributives are sentence components that are frequently used in Chinese, and the word order of multiple attributives constitutes an essential part of Chinese grammar as well as a major source of difficulty for learners of Chinese as a second language. Due to its structural complexity, the correct arrangement of multiple attributives poses significant challenges for non-native speakers. Although learners are introduced to attributives through formal instruction, many remain unfamiliar with the rules governing multiple attributive order. This study investigates the mastery of multiple attributive word order in Chinese among the 2022 cohort students of Gongtong Hope Language Institute and explores the factors influencing their performance. Drawing on previous theoretical studies on the relationships among multiple attributives, this research adopts a mixed-method approach, with data collected through test papers and questionnaires. The research procedure involved administering tests and questionnaires, followed by descriptive statistical analysis of test results and qualitative analysis of questionnaire responses to examine students’ mastery from three structural types: coordinate multiple attributives, successive multiple attributives, and interlaced multiple attributives. A total of 122 valid test papers and questionnaires were analyzed, and the results show that the students’ overall mastery of multiple attributive word order in Chinese reached only 51.37%, indicating that most students have not fully mastered this grammatical structure. The findings further reveal that learners’ difficulties are influenced by factors such as negative transfer from their mother tongue, textbook design, and learning motivation, which frequently lead to errors in attributive ordering, highlighting the importance of this study for improving the teaching of multiple attributives and providing pedagogical implications for more systematic instruction and targeted practice in Chinese language education.